The Effect of Islamic Work Ethic on the Quality of Employee Performance at PT. Karya Putra Surya Gemilang - Abdul Rohman; Andri Gunawan; Ismail Haqqi (Kusuma Negara Business School, 2020)
Human resources are one of the most strategic and important factors in organizing. Compared to other factors, human resources are the most valuable asset. A successful and effective organization is an organization with individuals in it who have good performance. An effective or successful organization will be supported by qualified human resources. Al-Qur'an and the Hadith recommends humans, especially Muslims, to spur themselves to work hard and try as much as possible, in the sense that a Muslim must have a high work ethic so that he can achieve success and succeed in pursuing his world life in addition to his afterlife. This study uses quantitative data analysis, meaning that all data is manifested in numbers and the analysis is based on statistical analysis. Data tabulation for each variable was carried out on the scores obtained using the help of the SPSS for Windows version 19.0. From the results of research and discussion based on analyzes and tests carried out on the effect of Islamic work ethic on the quality of employee performance at PT Karya Putra Surya Gemilang. This research can be used as input for the company at PT Karya Putra Surya Gemilang in improving the quality of employee performance, through the application of the concept of an Islamic work ethic where work is a translation of aqidah, work is based on knowledge and work by imitating the characteristics of Rasulullah SAW and following the instructions. His instructions, so as to increase the spirit of employee performance which can be used as an effort to achieve company goals which can be a company that is successful in its field, benefits others, and can also empower human resources who are professional, religious and have noble morals